2019
DOI: 10.1074/jbc.ra119.008903
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium transporter 1 (MAGT1) deficiency causes selective defects in N-linked glycosylation and expression of immune-response genes

Abstract: Magnesium transporter 1 (MAGT1) critically mediates magnesium homeostasis in eukaryotes and is highly-conserved across different evolutionary branches. In humans, loss-offunction mutations in the MAGT1 gene cause X-linked magnesium deficiency with Epstein-Barr virus (EBV) infection and neoplasia (XMEN), a disease that has a broad range of clinical and immunological consequences. We have previously shown that EBV susceptibility in XMEN is associated with defective expression of the antiviral natural-killer grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…Interestingly, we found defective glycosylation of certain ion transporters in XMEN samples, and Mg 2+ deficiency can affect glycosylation (14). The MAGT1 gene is conserved in unicellular eukaryotes such as yeast, indicating an ancient phylogenetic connection between glycosylation and Mg 2+ (12).…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Interestingly, we found defective glycosylation of certain ion transporters in XMEN samples, and Mg 2+ deficiency can affect glycosylation (14). The MAGT1 gene is conserved in unicellular eukaryotes such as yeast, indicating an ancient phylogenetic connection between glycosylation and Mg 2+ (12).…”
Section: Methodsmentioning
confidence: 78%
“…Protein glycosylation is a posttranslational modification critical for normal immune function (11). MAGT1 has high amino acid sequence homology with the human tumor suppressor candidate 3 protein (TUSC3) and the yeast oligosaccharyl transferase 3/6 (OST3/6) proteins that participate in the enzymatic complex that performs asparagine N-linked glycosylation (NLG) in the endoplasmic reticulum (ER) (12)(13)(14). Each OST complex has 1 catalytic subunit, either STT3A or STT3B, and multiple noncatalytic subunits creating distinct but complementary NLG enzyme complexes (15,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the molecular relationship to OST subunits and complexities of Mg 2+ suggested that pivotal manifestations of XMEN syndrome may rotate around defective glycosylation, in addition to or instead of alterations in Mg 2+ transport [ 171 ]. However, a study from the same group also showed that glycosylation is sensitive to Mg 2+ levels and that reduced Mg 2+ impairs immune cell function via the loss of specific glycoproteins [ 172 ].…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%
“…MagT1 deficiency leads to the absence of a T cell antigen receptor-stimulated Mg flux and attenuation of T cell activation [ 155 , 173 ]. Matsuda-Lennikov et al have reported that MagT1 mediates N-linked glycosylation and expression of immune-response genes in T cells [ 174 ].…”
Section: Mg Deficiency Induces Metabolic Derangementsmentioning
confidence: 99%